2009
DOI: 10.1534/genetics.109.109686
|View full text |Cite
|
Sign up to set email alerts
|

ACaenorhabditis elegansRNA-Directed RNA Polymerase in Sperm Development and Endogenous RNA Interference

Abstract: Short interfering RNAs (siRNAs) are a class of regulatory effectors that enforce gene silencing through formation of RNA duplexes. Although progress has been made in identifying the capabilities of siRNAs in silencing foreign RNA and transposable elements, siRNA functions in endogenous gene regulation have remained mysterious. In certain organisms, siRNA biosynthesis involves novel enzymes that act as RNAdirected RNA polymerases (RdRPs). Here we analyze the function of a Caenorhabditis elegans RdRP, RRF-3, dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
109
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(111 citation statements)
references
References 78 publications
2
109
0
Order By: Relevance
“…Sperm genes are also overexpressed in eri-1 and rrf-3 mutants (Asikainen et al, 2007), both of which encode Dicer complex components that produce 26G endo-siRNAs complementing spermatogenesis genes (Gent et al, 2009;Han et al, 2009;Pavelec et al, 2009). It has been proposed that spermatogenesis defects observed when impairing ERI-1, RRF-3 or the sperm-specific 26G-binding proteins ALG-3 and ALG-4 can be attributed to either under-or overexpression of sperm mRNAs (Conine et al, 2010;Gent et al, 2009;Han et al, 2009;Pavelec et al, 2009). This apparent discrepancy might have a simple resolution if an endogenous siRNA pathway represses sperm-specific transcription in adult hermaphrodites that have already undergone spermatogenesis, but promotes sperm-specific transcription in males and during the short window of spermatogenesis in hermaphrodites.…”
Section: Discussionmentioning
confidence: 99%
“…Sperm genes are also overexpressed in eri-1 and rrf-3 mutants (Asikainen et al, 2007), both of which encode Dicer complex components that produce 26G endo-siRNAs complementing spermatogenesis genes (Gent et al, 2009;Han et al, 2009;Pavelec et al, 2009). It has been proposed that spermatogenesis defects observed when impairing ERI-1, RRF-3 or the sperm-specific 26G-binding proteins ALG-3 and ALG-4 can be attributed to either under-or overexpression of sperm mRNAs (Conine et al, 2010;Gent et al, 2009;Han et al, 2009;Pavelec et al, 2009). This apparent discrepancy might have a simple resolution if an endogenous siRNA pathway represses sperm-specific transcription in adult hermaphrodites that have already undergone spermatogenesis, but promotes sperm-specific transcription in males and during the short window of spermatogenesis in hermaphrodites.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple endo-siRNA pathways in C. elegans, including the CSR-1 RNAi pathway (Claycomb et al 2009;Gu et al 2009), the WAGO RNAi pathway , and the ERI RNAi pathway Gent et al 2009;Han et al 2009;Vasale et al 2010). The biological roles of the endo-RNAi pathways in C. elegans remain largely uncharacterized.…”
Section: Discussionmentioning
confidence: 99%
“…A major known role of the WAGO endoRNAi pathway is in genome surveillance: the silencing of transposable elements, aberrant transcripts , and gene duplications (Vasale et al 2010;Fischer et al 2011). The ERI pathway has been implicated in regulating genes required for spermatogenesis and fertility (Gent et al 2009;Han et al 2009;Conine et al 2010), whereas the CSR-1 RNAi pathway has been recently shown to positively regulate histone mRNA expression (Avgousti et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these small RNAs start with G and are either 22 nt or 26 nt in length, reminiscent of C. elegans 22G-and 26G-RNAs. C. elegans 22G-RNAs function in chromosome segregation, transposon silencing, and gene regulation (Ambros et al 2003b;Lim et al 2003;Ruby et al 2006;Pak and Fire 2007;Sijen et al 2007;Claycomb et al 2009;Gent et al 2009;Gu et al 2009;van Wolfswinkel et al 2009;Vasale et al 2010;Zhang et al 2011) C. elegans has two classes of 26G-RNAs that regulate gene expression associated with spermatogenesis (Class I) and early zygotic development (Class II) Conine et al 2010;Gent et al 2010;Vasale et al 2010;Zhang et al 2011).…”
Section: Ascaris Endo-sirnas In Gametogenesis and Embryogenesismentioning
confidence: 99%